The Effect of Providing Education on Secondary Sex Changes During Puberty on Knowledge in Adolescent Girls in Man Insan Cendekia Gorontalo - Nurmelisa R. Djaini; Ika Wulansari; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2026)
In adolescence, a person experiences rapid development both physically, psychologically and socially. The most noticeable changes are physical changes that occur naturally and sometimes adolescents are unaware of these changes. Changes in puberty are related to the maturity of the reproductive organs, physical and sexual maturity, one of which is the development of secondary sex, but many adolescents do not know about the development of secondary sex, therefore, there is a need to make efforts to increase adolescent knowledge, one of which is by providing education. This study aims to analyze the effect of providing education about secondary sex changes during puberty on knowledge in adolescent girls at Man Insan Cendekia Gorontalo. The design of this study uses quantitative research using pre-experiment with a pre-test-post test without control group design. The population in this study is 60 young women at MAN Insan Cendekia. The sample was taken using the purposive sampling technique with a total of 38 respondents who met the inclusion criteria. The level of knowledge was measured using a knowledge questionnaire instrument. Data analysis was conducted using a paired t-test. The results of the study found that the p-value = 0.000 (<0.05), so it can be concluded that there is an effect of providing education about secondary sex changes during puberty on knowledge in adolescent girls at Man Insan Cendekia Gorontalo. The conclusion is that education about secondary sex changes significantly increases adolescents' knowledge of secondary sex development as it relates to their physical development.